Aging techniques for deep vein thrombosis: a systematic review. (March 2015) - Dharmarajah, B; Sounderajah, V; Rowland, SP; Leen, ELS; Davies, AH
Deep vein thrombosis is common with an incidence of 1 in 1000. Acute thrombus removal for extensive proximal deep vein thrombosis using catheter-directed techniques highlights the need for accurate assessment of thrombus age. This systematic review summarises experimental and clinical evidence of imaging techniques for aging deep vein thrombosis. Ultrasound elastography and magnetic resonance imaging were highlighted as the most studied imaging modalities. Elastography was shown to distinguish between acute and chronic clots, despite demonstrating difficulty in accurate aging of clots older than 10 days in rat models. Elastography is noted as a feasible adjunct to current first-line imaging for deep vein thrombosis using duplex ultrasonography. Combinations of magnetic resonance imaging techniques can identify acute, sub-acute and chronic thrombi using endogenous contrast agents and provide objective standardisation of the diagnostic process, with reduced onus upon operator dependency. Further validation is required of these novel imaging techniques prior to clinical implementation for deep vein thrombosis aging.